Analysis of Maqashid Shariah Implementation in the Financial Performance of Islamic Rural Banks (BPRS) in Indonesia - M Andika Hariz Hamdallaha; Bambang Sukamto (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
AbstractThis study examines the application of Maqashid Shariah within the financial performance framework of Islamic Rural Banks (BPRS) in Indonesia by evaluating the extent to which profitability, operational efficiency, liquidity management, and credit risk influence Maqashid Shariah outcomes. Using panel data from 2015–2024 and employing the EViews regression approach, the research integrates both financial indicators and the Maqashid Shariah Index to measure the alignment of BPRS operations with the objectives of Shariah, including the preservation of wealth, promotion of justice, development of human capability, and enhancement of social welfare. The findings show that profitability significantly improves Maqashid Shariah performance, demonstrating that financial strength enables banks to invest more extensively in welfare-oriented initiatives. Liquidity efficiency, measured through Financing to Deposit Ratio (FDR), also displays a positive influence, indicating that productive financing contributes to community empowerment and financial inclusion. Conversely, operational inefficiency and high non-performing financing reduce the bank’s ability to deliver Shariah-driven outcomes, reflecting the importance of cost management and risk governance. Overall, the results highlight that financial sustainability and Maqashid Shariah are mutually reinforcing rather than competing objectives. The study underscores the need for BPRS to strengthen governance, improve risk management, and adopt strategic innovations to optimize their contribution to ethical and welfare-driven economic development. The findings have implications for policymakers, regulators, and practitioners seeking to enhance the role of Islamic rural banks in advancing Shariah-compliant socio-economic transformation. Keywords: Maqashid Shariah, BPRS, financial performance, Islamic banking, welfare outcomes.